Investigation of optimum milling parameters in micro dimples machining - Haizad, Hassim; Ahmad Rosli, Abdul Manaf (Penerbit UMP, 2022)
This research used a carbide ball nose end mill cutting tool to fabricate a micro dimple on the aluminium block. The problem is that the micro dimple should be fabricated with a better surface finish which is related to surface integrity and form accuracy of the dimple. The objective is to study the optimum CNC milling parameters for the micro dimple fabrication and analyse the surface integrity and form accuracy of the dimple. Based on three different parameters which is depth of cut, feed rate, and spindle speed, the better surface roughness and the diameter, depth of micro dimple are experimented using the carbide cutting tools to fabricate micro dimple and analyse the data using 3D confocal microscope. The better surface roughness, high form accuracy and surface integrity of micro dimple structure were achieved with the optimum CNC milling parameters. The high spindle speed, low depth of cut and low feed rate showed the best results for the surface roughness and form accuracy. The proposed parameters were high spindle speed of 3600 RPM, low depth of cut 0.25mm and low feed rate of 50mm/min.